Perancangan UI/UX Aplikasi Untuk Meningkatkan Efisiensi Pemesanan Jasa Fotografi Terhadap Maka Studio Menggunakan Metode Design Thinking - Febriansyah; Ruly Dwi Arista; Randi Rian Putra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
As technology advances increasingly rapidly, especially in the field of e-commerce, Studios experience difficulties in handling orders for photography services. Ordering methods that still rely on WhatsApp (WA) show inefficiency and lack of optimization. This research focuses on designing the UI/UX of the application with the aim of increasing the efficiency of ordering photography services at Maka Studio. The testing process involves two methods, namely SUS (System Usability Scale) and analysis of data collected through questionnaires. The research subjects consisted of 10 respondents who were potential Maka Studio customers and 20 respondents among students. This research applies the Design Thinking method, through the stages of Empathize, Define, Ideate, Prototype, and Test. These stages aim to understand user needs, identify problems, come up with solution ideas, create prototypes, and test prototypes. The research results show that the application of design thinking was successful in creating the Maka Studio online booking system. This system is expected to be able to overcome various obstacles previously experienced by customers when placing orders at photo studios. Usability testing results shows that the UI/UX design of the photography services ordering application has achieved excellent results and meets user expectations. This can be seen from the majority of respondents who gave positive assessments of various aspects of the application, as well as the SUS test results with an average score of 94.3%.